OFF-SEASON STRATEGIES TO IMPROVE SOIL PHYSICAL ATTRIBUTES IN A NO-TILL SYSTEM IN THE BRAZILIAN CERRADO - FERREIRA, RANIER VIEIRA; MORAES TAVARES, ROSE LUIZA; PAIVA FILLHO, SILVIO VASCONCELOS; MARASCA, INDIAMARA; SILVA, ALESSANDRO GUERRA (REVISTA BRASILEIRA DE MILHO E SORGO, 2020)
In the central region of Brazil, sorghum and maize are considered viable crop alternatives to be cultivated during off-season periods, mainly for the production of grains in succession to the cultivation of soybeans and intercropping with brachiaria grasses. This study aimed to evaluate the physical soil qualities of the soil from an area with different off-season management histories (monoculture or agricultural intercropping). Maize, sorghum and brachiaria crops have been cultivated under no-tillage system. The experiment was conducted using a randomized complete block design, with four replications. The treatments included: monoculture or intercropping between sorghum and brachiaria (first off-season strategy) or maize and brachiaria (second off-season strategy). The following physical properties of the soil were evaluated: soil bulk density, porosity, soil resistance to penetration, soil moisture and texture and the contents of organic carbon, which were analyzed at 0-20, 20-40 and 40-60 cm deep. In the off-season, the cultivation of single brachiaria promoted a greater amount of dry matter when compared with sorghum- brachiaria or maize-brachiaria intercropping. The topsoil presented better physical quality when compared with the adjacent layers under no-tillage system. The use of brachiaria combined with sorghum or maize tends to improve the macro and microporosity of the soil.